The Definition of The Psychological Pressure on Children by The Parents at The Post-Divorce Stage (European Journal of Behavioral Sciences, 2020)
In this article we have tried to present our research in this field, drawing on a parallel with world experience, research and obtained data.It is well known that the innate desire to have a relationship with parents is one of the most powerful instincts of man, perhaps surpassed only by the instinct of survival and the instinct of protection own children. Among normal children, this instinct is rarely suppressed if there is no stimulating influence.In our article we have tried to show that alienation is more widespread and depressing for children and parents than previously thought. It is more important to raise this issue these days because it may seem strange that all over the world, every day, every hour, is expressing their views on the protection of children's rights, many laws and international conventions are being adopted, but the children still remain the vulnerable and defenseless ring.A thorough study of the key elements of parent alienation in research literature has revealed that it contains elements of maltreatment with children. At the same time, our research has shown that the more a child persistently insists on not being in touch with the other parent, the greater the pressure on the child from the other parent. Therefore, parental alienation requires relevant measures for children protection.A notorious factor should be the involvement and taking the responsibility of competent structures, rather than avoiding or ignoring such phenomena.